Budaya Manggarai sebagai Ruang Dialog Intereligius dalam Masyarakat Multireligius - Kristinus Sembiring; Yulius Edward Indra Doris; Yohanes Alfrid Suardi Aris; Elisabeth Serfiana Asti (Perspektif, 2026)
This article explores the role of Manggarai culture as a framework for facilitating interfaith dialogue in the Manggarai region. The primary focus of the research is to understand how local cultural values in Manggarai can act as a bridge enabling people of different faiths to interact harmoniously. Although religious diversity exists within Manggarai society, this article seeks a deeper understanding of how local culture can unite them through symbols, traditions, and religious practices that collectively form the foundation for dialogue. This is important due to the scarcity of research specifically highlighting the role of Manggarai culture in the context of interfaith dialogue. By focusing on this gap, this study opens the door to a deeper understanding of the contribution of local culture to the formation of positive and inclusive interfaith dialogue. The research method employs an anthropological qualitative approach that details religious practices and cultural values playing a key role in bridging understanding between different religious groups. Findings from this study indicate that Manggarai culture plays a significant role in facilitating interfaith dialogue in Manggarai. Furthermore, Manggarai customs that value diversity are also a crucial factor in fostering harmonious interfaith dialogue. This enriches interfaith dialogue theory through contextual and “lived religion” approaches. This study reinforces the idea that socio-cultural spaces can function as “shared spaces” that transcend the boundaries of religious identity.